The impact of stress on the quality of pork - I. Y. Stronskyi; M. R. Simonov; Y. S. Stronskyi; M. M. Akymyshyn (Біологія тварин, 2021)
The quality and safety of pork is influenced by many factors before and after slaughter. Complex of biochemical and physicochemical processes take place in the maturation of the meat. One of the key factors that affect the quality of meat from slaughtered animals is the level of cortisol in the blood, because glucocorticoid hormone is the trigger for the development of a chain of stress biochemical reactions. This paper contains results of examination of the blood concentration of cortisol and lactate and meat pH. Samples were taken in two animal groups. The first one constituted of industrially reared and slaughtered animals, and the other group consisted of animals grown and slaughtered on small farms. In the blood of industrially reared pigs in comparison with domestic animals, the concentration of cortisol is significantly higher by 39.9% (P˂0.05), as well as the level of lactate — 2.3-fold (P˂0.01). The main reason is due to the stress experienced by animals during transportation and pre-slaughter handling. There is a marked difference between the maximum and the minimum plasma level of cortisol in pigs within one group. Under stress the breakdown of glucose and glycogen in the liver and muscles took place in anaerobic condition with formation of lactate. At 1, 24 and 48 hours of pork meat maturation in case of industrial rearing and slaughtering, compared to domestic, the pH of meat was lower. Obtained results gives the possibility to suggest the lower quality of the industrially reared and slaughtered pork compared with domestic.